The association of panic and hyperventilation with psychogenic non-epileptic seizures: A systematic review and meta-analysis. (July 2018) - Indranada, Alaric M.; Mullen, Saul A.; Duncan, Roderick; Berlowitz, David J.; Kanaan, Richard A.A.
Highlights: Panic attacks vary widely in PNES with meta-analysis showing a moderate association. Panic symptoms in PNES are mostly somatic, with affective symptoms less common. Meta-analysis showed hyperventilation moderately successfully induces PNES events. Abstract: Introduction: Psychogenic Non-Epileptic Seizures (PNES) are events that appear epileptic but are instead thought to have a psychological origin. Increased rates of several psychiatric disorders have been reported in PNES, including anxiety and panic disorders. Some theories suggest panic and/or hyperventilation have aetiological roles in PNES, though these remain unproven. Methods: We conducted a systematic review of associations of panic and hyperventilation with PNES using Ovid Medline and PubMed, and a meta -analysis where appropriate. Results: We found eighteen studies reporting rates of panic in PNES and eight studies reporting hyperventilation. The reported rate of panic attacks in PNES ranged from 17% to 83%, with physical symptoms more commonly reported, and affective symptoms less so. 'Dizziness or light-headedness' was found to be more prevalent than 'fear of dying' by random-effects meta-analysis (68% vs. 23%). A proportion meta-analysis found a weighted occurrence of 20% of panic disorder in PNES. A pooled meta-analytic rate of PNES events following voluntary hyperventilation induction was 30%, while the clinically observed rates of peri-ictal hyperventilation in PNES without induction varied from 15 to 46%. Conclusions: Previous studies have reported moderate rates of association of panic in PNES, though the proportions varied considerably across the literature, with physical symptoms more commonly reported than affective. Hyperventilation is an effective inducer of PNES events in a minority, and can be observed occurring in a minority of patients without induction. These results support an important, albeit not essential, role for panic and hyperventilation in the pathogenesis of PNES events.